Synchronous Oligometastatic Non-small Cell Lung Cancer Managed With Curative-Intent Chemoradiation Therapy: Long-term Outcomes From a Single Institution - Yegya-Raman, Nikhil (Adv Radiat Oncol, 2019)
PURPOSE: We examined long-term clinical outcomes among patients with synchronous oligometastatic non-small cell lung cancer (NSCLC) treated at our institution with definitive thoracic chemoradiation therapy (CRT) and local therapy to all oligometastatic lesions. METHODS AND MATERIALS: A retrospective review identified 38 patients with synchronous oligometastatic NSCLC (≤3 metastatic lesions) who were treated with definitive CRT to the primary tumor and regional lymph nodes between 1999 and 2017 at our institution. Of the 38 patients, 27 patients (71%) received induction chemotherapy, all of whom responded or stabilized with initial systemic therapy before consideration of CRT. Most patients received chemotherapy concurrently with radiation therapy (n = 32; 84%) and local therapy to the metastatic disease site(s) (n = 34; 89%). We assessed patterns of progression or failure, overall survival (OS), progression-free survival (PFS), and toxicities. RESULTS: The median follow-up duration was 54.9 months. Most patients (84%) presented with N2 to N3 disease. The brain or central nervous system was the most common site of disease progression and occurred in 16 of 28 patients (57%) experiencing any progression and 10 of 16 patients (63%) who initially presented with brain oligometastases. Median OS was 21.1 months (95% confidence interval [CI], 15.6-49.0 months), and median PFS 9.7 months (95% CI, 8.2-14.4 months). The 1-, 2-, and 4-year OS rates were 75.7%, 45.0%, and 33.7%, respectively. On multivariate analysis, both locoregional progression (hazard ratio: 5.8; 95% CI, 2.2-15.0; P = .0003) and distant progression (hazard ratio: 6.0; 95% CI, 2.3-15.4; P = .0002), when treated as time-dependent covariates, were associated with inferior OS. Grade ≥3 esophagitis occurred in 9% and grade ≥3 pneumonitis in 5% of patients with evaluable data. CONCLUSIONS: Patients with synchronous oligometastatic NSCLC and a high regional nodal burden treated with definitive thoracic CRT experienced favorable survival outcomes and low toxicity. At our institution, treating oligometastatic disease with CRT after systemic therapy is incorporated into the treatment plan from the onset of therapy, and we monitor the neuraxis closely for progression during and after treatment. Future research should focus on novel treatment combinations, such as immunotherapy or targeted systemic therapy as appropriate to further improve tumor control and survival.